Key for identification of Cladocera of the subfamily Aloninae (Anomopoda: Chydoridae) from South-East Asia - Sinev, Artem Y. (Zootaxa, 2016)
An identification key for Cladocera of subfamily Aloninae (Anomopoda: Chydoridae) of South-East Asia is provided. The key includes 42 species known from the region to date, and encompass all recent changes in taxonomy of the subfamily Aloninae. Drawings and descriptions of diagnostic characters for each species are provided. This is the first identification key for Aloninae of the region published in the last forty years.